Constitutive model for full-range elasto-plastic behavior of structural steels with yield plateau: Formulation and implementation. (15th September 2018) - Hu, Fangxin; Shi, Gang; Shi, Yongjiu
Highlights: A new constitutive model for structural steels with yield plateau is formulated. The model correctly traces the cyclic softening and hardening behavior. Consistency conditions are deduced to facilitate the calibration of parameters. The model is successfully implemented into FE software ABAQUS/Standard. Abstract: Performance-based engineering methodologies allow for the design of more reliable seismic resistant structures. Nonetheless, to implement this technique, an accurate constitutive model to predict the elasto-plastic behavior of structural steel components or systems under various loadings is needed to properly evaluate their strength, deformation and energy absorption capacities in case of severe earthquakes. Such a model should also be relatively simple to use for practical purposes in engineering. With these objectives in mind, a new constitutive model is formulated to describe the elasto-plastic behavior of structural steels with yield plateau. This model uses nonlinear kinematic hardening to trace well the significant Bauschinger effect in full-range cyclic loadings, and couples nonlinear isotropic hardening with a memory surface in the plastic strain space to account for the stabilization phenomena of cyclic softening and hardening. An impermanent bounding surface in the stress space is employed to correctly describe the yield plateau response. The consistency condition is investigated in detail, which results in implications that will greatly facilitate the calibration of material dependent parameters. The implementation technique is also presented for three-dimensional and two-dimensional problems respectively. Using the resulting integration algorithms, the proposed constitutive model is successfully incorporated into ABAQUS/Standard by the UMAT subroutine feature.